Pengaruh Kondisi Fasilitas (Facilitating Condition) dengan SIAKAD (Sistem Informasi Akademik) berbasis Online sebagai Variabel Moderasi Terhadap Kinerja Dosen (Studi Kasus di UIN Syuhada Padangsidempuan Program Studi Tarbiyah dan Ilmu Keguruan) - Sarah Madaniah; Parapat Gultom (Multiverse: Open Multidisciplinary Journal, 2023)
This research aimed to examine the impact of facilitating conditions on the performance of lecturers within the Tarbiyah and Teacher Training Study Program (a case study conducted at UIN Syuhada Padangsidempuan). It also considered the online-based SIAKAD variable as a moderating factor. The study specifically investigated the influence of facility variables (X1) and the online-based SIAKAD (Xm) on lecturer performance. Employing a quantitative approach with an associative perspective, the research utilized a non-probability sampling technique, encompassing a saturated sample (census), which involved all 67 lecturers. The findings indicate that facilities (X1) exhibit a significant positive impact on lecturer performance, while online-based SIAKAD (Xm) similarly positively influences lecturer performance. However, the online-based SIAKAD variable does not appear to act as a moderator, enhancing the effect of the facility variable (X1) on the lecturer performance variable (Y), as evidenced by the insignificance value of 0.631 > 0.05.